2011
DOI: 10.1099/mic.0.045286-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide degradation by Pseudomonas pseudoalcaligenes CECT5344 involves a malate : quinone oxidoreductase and an associated cyanide-insensitive electron transfer chain

Abstract: The alkaliphilic bacterium Pseudomonas pseudoalcaligenes CECT5344 is able to grow with cyanide as the sole nitrogen source. Membrane fractions from cells grown under cyanotrophic conditions catalysed the production of oxaloacetate from L-malate. Several enzymic activities of the tricarboxylic acid and glyoxylate cycles in association with the cyanide-insensitive respiratory pathway seem to be responsible for the oxaloacetate formation in vivo. Thus, in cyanide-grown cells, citrate synthase and isocitrate lyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…13 also assimilates 3-cyanoalanine, and this compound is the inducer of the nitrilase activity (47). In contrast, it has been reported that in Pseudomonas pseudoalcaligenes CECT 5344 3-cyanoalanine does not induce the cyanide assimilation pathway (40), and here we demonstrate that the inducer of the nit4 gene is clearly cyanide (Fig. 1B and 6A) and that 3-cyanoalanine is much more efficiently assimilated in the presence of cyanide (Fig.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…13 also assimilates 3-cyanoalanine, and this compound is the inducer of the nitrilase activity (47). In contrast, it has been reported that in Pseudomonas pseudoalcaligenes CECT 5344 3-cyanoalanine does not induce the cyanide assimilation pathway (40), and here we demonstrate that the inducer of the nit4 gene is clearly cyanide (Fig. 1B and 6A) and that 3-cyanoalanine is much more efficiently assimilated in the presence of cyanide (Fig.…”
Section: Discussionmentioning
confidence: 43%
“…A putative nitrilase gene homologous to the gene encoding the 3-cyanoalanine nitrilase described in plants (nit4) was detected among the four putative nitrilase genes in the genome of P. pseudoalcaligenes CECT 5344 (38). Moreover, P. pseudoalcaligenes CECT 5344 has been reported to be able to assimilate 3-cyanoalanine (40). Since there are not published antecedents concerning either the assimilation pathway of 3-cyanoalanine in this strain or its role in cyanide assimilation, the presence of a putative 3-cyanoalanine nitrilase activity was studied.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, few studies have evaluated the influence of inorganic supports on the BDS activity and using polymers as the support for bacterial strain for BDS never have been observed [32,33]. Pseudomonas species are able to grow with cyanide as the sole nitrogen source and several enzyme activities of these bacterial strains were significantly higher than those observed with other nitrogen sources [34]. Also the bacterial cells exhibited a greater extent and rate of biodegradation in the presence of ferricyanide as the terminal electron acceptor compared to the individual cells [35].The purpose of this study is to investigate biodesulphurization ability of P. aeruginosa supported on polyethylene in the presence of potassium hexacyanoferrate(III) in thiophene biodegradation as an aromatic sulphur model compound of crude oil.…”
Section: Introductionmentioning
confidence: 99%